PENERAPAN PENDEKATAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN 039 SIARANG-ARANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Sri Dewis '; Zariul Antosa Antosa; Damanhuri Daud Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research is motivated by low yields social studies students, with an average grade of 67.5. While the completeness criteria Minimum value (KKM) IPS is 70 Among students who were 18 people only 5 students who reached the KKM with classical completeness 28%. This research is Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS 039 third grade students of SDN Siarang-arang Kecamatan Pujud Rokan Hilir the inquiry approach. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of a study in which the initial data obtained by students who completed as many as 11 people (61.11%) with an average value of 60.11 and then the students who complete the first cycle increased to 14 people (77.77%) with average value of 70.83 and the second cycle continues to increase to 16 people (88.8%) with an average value of 78.33. Increased activity of students and teachers, where the first meeting of the first cycle of activity students 66.6% and 70.8% of teachers. At the second meeting of the student activity 79.1% and 79.1% of teachers. At the first meeting siklus II student activities 87.5% and 87.5% of teachers. At a meeting of the student keduaaktivitas 95.8% and 91.6% of teachers. The results of the study in the third gradethe 039 SDNSiarang-arang Kecamatan Pujud Rokan Hilir prove that the application of the inquiry approach can improve student learning outcomes IPS SDN III 039 Siarang-arang Kecamatan Pujud Rokan Hilir. Keywords: Inquiry Approach, IPS Learning Outcomes